THE IMPLEMENTATION OF WORD WALL STRATEGY IN TEACHING WRITING DESCRIPTIVE TEXT - Darliani, Yani; Agustina, Cica Farida (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2019)
Sometimes students experience writing problems, attempt to understand the text and get confused to begin describing because they lack vocabulary and concept. The study was directed at finding out the Word Wall approach introduced in teaching descriptive text to high school vocational learners and finding answers for learners in learning descriptive text to implement the Word Wall approach. The study was carried out at one of Bandung's vocational high schools. In this study, the descriptive qualitative method was used. The research participants are a first-grade teacher and five students. The information was acquired as the study tool by observation and interview. Word wall approach is one of the strategies that can be used in the learning process of teaching. Word Wall approach was a strategy consisting of a group of phrases that placed a distinct background color on the wall that corresponds to a distinct curricular goal. The teacher provides learners with important phrases or clues to readily create their thoughts. The outcome demonstrates that all respondents responded positively to the approach of Word Wall. Implementing Word Wall approach has been useful in teaching for high school vocational learners and makes writing descriptive text enjoyable for learning.